Sinuplastia con balón - Nazar S., Rodolfo; Kim, Yoon Ah; Alvo V., Andrés (Revista Hospital Clínico Universidad de Chile, 2011)
The balloon sinuplasty or sinus ostia balloon dilation is a surgical therapeutic instrument used in patients with refractory chronic rhinosinusitis, which can be performed as an isolated procedure or simultaneously with the functional endoscopic surgery (hybrid technique). Although there is a lack of prospective randomized controlled studies and only few studies in pediatric population, itseems to be an efficient and safe tool. It stands out because of its less invasiveness, therefore, especially useful in frontal sinus, in revision surgery, and making possible office setting sinus treatment.